2021
DOI: 10.1038/s41598-021-02859-y
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating features of OCT angiography in diabetic macular edema

Abstract: The purpose of current study was to evaluate different optical coherence tomography angiography (OCTA) metrics in eyes with diabetic retinopathy with and without diabetic macular edema (DME). In this retrospective study, macular OCTA images of eyes with non-proliferative or proliferative diabetic retinopathy were evaluated. Vascular density, vascular complexity and non-perfusion densities were compared between eyes with and without DME. One-hundred-thirty-eight eyes of 92 diabetic patients including 49 eyes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…1A,B). Manual segmentation error correction was also implemented for various retinal layers, as described elsewhere, 34 to enhance the accuracy of the measurements further. This advanced imaging approach allows for non‐invasive visualization and quantification of the retinal vasculature, enabling a comprehensive assessment of vascular characteristics and their variations across different retinal regions.…”
Section: Methodsmentioning
confidence: 99%
“…1A,B). Manual segmentation error correction was also implemented for various retinal layers, as described elsewhere, 34 to enhance the accuracy of the measurements further. This advanced imaging approach allows for non‐invasive visualization and quantification of the retinal vasculature, enabling a comprehensive assessment of vascular characteristics and their variations across different retinal regions.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the perfusion state of macular vessels might not be changed. Mirshahi et al [19] found that macular edema was associated with more non-perfusion in OCTA compared to dry macula. Therefore, the inability of anti-VEGF treatments to improve capillary non-perfusion could be a reason for recurrent DME following intravitreal injection of aflibercept.…”
Section: Correlation Analysis Of Factorsmentioning
confidence: 99%
“…Yalçın and Özdek ( 59 ) found that patients with more severe DME had a 1.04-fold greater chance of having macular ischemia on FA, and postulated that macular ischemia would become more likely as the cyst’s diameter grows. Furthermore, Mirshahi et al ( 60 ) found that the presence of DME was associated with more extensive CNP when compared to DR eyes with no macular edema.…”
Section: The Role Of Capillary Non-perfusionmentioning
confidence: 99%